Crosstalk of ferroptosis and oxidative stress in infectious diseases - Hu, Yibao; He, Bisha; Cao, Qian; Li, Yue; Tang, Yun; Cao, Ting; Peng, Binfeng; Zhou, Xiangping; Liu, Shuangquan (Frontiers in Molecular Biosciences, 2023)
Ferroptosis is a type of programmed cell death that pathogens can leverage to enhance their replication, transmission, and pathogenicity. Hosts typically combat pathogenic infections by utilizing oxidative stress as a defense mechanism. Nonetheless, some pathogens can trigger considerable oxidative stress while infecting, inducing an intense inflammatory response in the host's immune system and activating cell death. The process of ferroptosis is closely linked to oxidative stress, with their interaction exerting a substantial impact on the outcome of infectious diseases. This article presents an overview of the interrelated mechanisms of both Ferroptosis and oxidative stress in infectious diseases, identifying potential targets for treating such diseases in the context of their interaction.